Spray‐dried porcine plasma improves feed intake of weaned piglets subjected to heat stress. Issue 3 (18th February 2019) - dos Santos Cerqueira, Luis Gustavo; Schinckel, Allan Paul; Silveira, Hebert; Kuribayashi, Thiago Hiroshi; Moreira, Rennan Herculano Rufino; Lisboa, Ítalo de Oliveira; Cantarelli, Vínicius de Souza; Pospissil Garbossa, Cesar Augusto
Abstract: The objective of this study was to evaluate the effects of spray‐dried porcine plasma (SDPP) on performance, measurement of thyroid hormones triiodothyronine (T3) and thyroxine (T4), body temperature and relative organ weights of weaned piglets exposed to a heat stress or a thermoneutral environment. One hundred and forty‐four piglets with initial BW of 5.82 ± 0.33 kg (28 d old) were used. The experimental design was a 4 x 2 factorial arrangement, four plasma levels (0.0, 2.5, 5.0 and 7.5%) and two environments (34º [heat stress (HS)] and 24°C [thermoneutral (TN)]). SDPP was fed from weaning (28 d of age) to the end of the trial (piglets were weighed at the beginning, 7, 21 and 35 days of trial). Rectal, neck, shoulder and leg temperatures were measured every seven days. At 21 days of trial, one piglet per pen was slaughtered to determine the weight of the carcass and organs. Blood samples were collected at 18 and 35 days of trial to determine levels T3 and T4. The rectal, neck, shoulder and leg temperatures were increased ( p < 0.05) 0.4, 1.5, 1.0 and 1.3ºC, respectively, and relative weight of the lungs ( p < 0.05) and total T3 ( p < 0.05) were decreased 0.001 kg/kg and 0.19 ng/dl, respectively, for pigs in the HS environment. The estimated inclusion of 5.1% of SDPP had the greatest ( p < 0.05) weight gain during the first week, and throughout the nursery phase, the 5% of inclusion had a tendency of improvement ( p = 0.075), regardless of ambient temperature. For the entire period, pigs reared in the HS environment had the greatest ( p < 0.05) estimated feed intake by the quadratic regression with the inclusion of 4.3% of SDPP.